Meningkatkan Peran Serta Masyarakat dalam Menyelesaikan Permasalahan Pada Masa Pandemi di Polda Jatim : Studi Polresta Malang Kota - Jarot Prianggono (Jurnal Pengabdian Kepada Masyarakat Kalam, 2023)
The Covid-19 pandemic has changed the order in society. Community Service Activities (dianmas) are one of the Tri Dharma of higher education that must be carried out by students. Therefore, one of the important roles of universities is to provide continuous assistance and collaboration to realize community participation so that they can have independence in solving problems in the future. the Covid-19 pandemic. One way is to carry out community service activities (Dianmas).